Information measures for the stochastic Gompertz growth model - Rupšys, Petras (Lietuvos matematikos rinkinys, 2008)
In this paper we investigate the Shannon’s, Fisher’s and Tsallis’ information measures for the Gompertz type stochastic process. We study the information measures of the stationary and non-stationary Gompertz type densities associated to the three parameters: intrinsic growth rate, saturation measure and noise amplitude. Finally we simulate the confidence interval for the value of all information measures. The results are implemented in the symbolic algebra language MAPLE.